1993
DOI: 10.1037/h0078827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sentence form on the construction of mental plans from procedural discourse.

Abstract: Memory for procedural discourse was examined in two experiments. In Experiment 1, memory was assessed using recall; in Experiment 2, a recognition test was used. In both experiments, the memorability of three types of action statements were compared: a transitive verb form, in which the action was described by a main clause; a verbal adjective form, in which the action was indicated by an adjective derived from a verb; and an implicit action form, in which the action was only implied. Information associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Thus, in the domain of Cognitive Psychology, research about procedure learning related to the comprehension of instructions (see [10], in press) generally shows that in the first steps of learning (i.e., when the procedure is still unknown), the individual proceeds by the elaboration of one or several intermediate mental representations from the presented instructions in order to carry out the described actions, which is time and cognitive resources consuming (see [16], [5] and a review of different models [9](in press)). Then, procedural knowledge is considered acquired when the task, the material or the procedure are so familiar that it becomes possible to recover the procedure directly from memory [18].…”
Section: Assessment Of Procedural Learning With the Gvt Environmentmentioning
confidence: 99%
“…Thus, in the domain of Cognitive Psychology, research about procedure learning related to the comprehension of instructions (see [10], in press) generally shows that in the first steps of learning (i.e., when the procedure is still unknown), the individual proceeds by the elaboration of one or several intermediate mental representations from the presented instructions in order to carry out the described actions, which is time and cognitive resources consuming (see [16], [5] and a review of different models [9](in press)). Then, procedural knowledge is considered acquired when the task, the material or the procedure are so familiar that it becomes possible to recover the procedure directly from memory [18].…”
Section: Assessment Of Procedural Learning With the Gvt Environmentmentioning
confidence: 99%
“…Although the effect of prior knowledge on text recall is well documented (Moravcsik & Kintsch, 1993;McNamara, Kintsch, Songer, & Kintsch, 1996), its effect on sentence recognition tasks remains unclear. Chiesi et al (1979) showed that the recognition performances of high-knowledge subjects were better than those of lowknowledge subjects, whereas Dixon and colleagues (Dixon, Faries, & Gabrys, 1988;Dixon, Harrison, & Taylor, 1993) found that, in contrast to recall results, recognition performances did not vary as a function of background reading. The finding of Dixon et al, suggests that recall and recognition are differentially sensitive to aspects of the mental representation and that recall tasks require subjects to have a semantic representation of the text, whereas recognition tasks require them to be able to compare the surface structure of two sentences.…”
Section: Introductionmentioning
confidence: 88%
“…However, their study also suggested that this effect occurs only if the information describes the internal functioning of the product, not when it merely stresses motivational aspects or general principles. Experiments by Dixon et al showed no effect of system information on how accurately subjects chose the actions needed to complete a task [7]. However, they did show an effect of system information on the recall of actions that needed to be performed.…”
mentioning
confidence: 91%